2003
DOI: 10.1002/jclp.10188
|View full text |Cite
|
Sign up to set email alerts
|

Measuring coping style and resistance among Spanish and Argentine samples: Development of the Systematic Treatment Selection Self‐Report in Spanish

Abstract: This article reports the reliability and validity of the Coping Style and Resistance subscales of the Systematic Treatment Selection Self-Report (STS-SR) scale after its translation to Spanish. The English versions of the STS system identify eight empirically derived patient variables that have been found to moderate the effects of various classes of mental health treatment procedures. Research on these dimensions as treatment indicators, as assessed both by clinicians and through patient self-reports, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…In Argentina and Switzerland, matching patterns parallel what has been found among US participants (Beutler, ; Beutler, Mohr, Grawe, Engle, & MacDonald, ). In these countries, patient CS seems to follow the same interactive parameters as is true in the United States (Corbella et al, ). It has also been found that the patterns of influence apply to men and women, but insufficient research has been conducted on clients of diverse sexual orientations, religious commitments, and other intersecting dimensions of culture.…”
Section: Diversity Considerationsmentioning
confidence: 81%
See 1 more Smart Citation
“…In Argentina and Switzerland, matching patterns parallel what has been found among US participants (Beutler, ; Beutler, Mohr, Grawe, Engle, & MacDonald, ). In these countries, patient CS seems to follow the same interactive parameters as is true in the United States (Corbella et al, ). It has also been found that the patterns of influence apply to men and women, but insufficient research has been conducted on clients of diverse sexual orientations, religious commitments, and other intersecting dimensions of culture.…”
Section: Diversity Considerationsmentioning
confidence: 81%
“…What can be said from the available research is that, at least among Spanish speakers in Argentina and Spain, CS can be translated without losing reliability (Corbella et al, ). In Argentina and Switzerland, matching patterns parallel what has been found among US participants (Beutler, ; Beutler, Mohr, Grawe, Engle, & MacDonald, ).…”
Section: Diversity Considerationsmentioning
confidence: 99%
“…Some cross‐cultural comparisons of patient reactance × therapist directiveness have been explored by research. While similarity to North American samples is the norm among South American and European studies (e.g., Beutler et al, ; Corbella et al, ), there are some indications of differences among Asian and non‐Asian populations (e.g., Beutler, ; Song et al, ). To date, the patterns related to reactance seem to transcend geographic and ethnic boundaries, but some distinctiveness appears also to be present among Asian groups.…”
Section: Diversity Considerationsmentioning
confidence: 99%
“…The STS-Clinician Rating Form (STS-CRF; Corbella et al, 2003, Fisher et al, 1999) initially developed to identify client presenting problems and client mediating and moderating traits which were identified in the step one was updated. The revised scale, the STS/innerlife (Beutler, Williams, & Norcross, 2008) offers reliable measurement of the surviving constructs with proven ability to predict change.…”
Section: Measures and Methods Used To Test Stsmentioning
confidence: 99%